Adaptabilidade, estabilidade e tolerância de acessos de meloeiro à salinidade - Ferreira, Alex Rodrigues (Universidade Federal Rural do Semi-Árido, 2016)
The aim of this study was to evaluate the adaptability and stability of melon accessions to salinity. Thirteen accessions and three commercial hybrids in four saline conditions in a randomized complete block design with three replications and the plot of a row of eight plants spaced 2.0 x 0.4 m. The environments are differentiated as the electrical conductivity of irrigation water, and set four salt levels (S1: 0.91 dS m-1, S2: 2.14 dS m -1, S3: 2.90 dS m-1, and S4: 3.92 dS m-1). The variables analyzed were: average fruit weight, number of fruits, productivity, pulp thickness, firmness of soluble solids and pulp. We utilized the GGE Biplot methodology for identifying adaptability and stability genotypes. We used the production efficiency index to identify tolerant genotypes salinity. Accessions A-29, A-50, A-13, A-14, A-39, Najd I and A-7 are tolerant to salinity and have features such as prolificacy, pulp thickness and firmness pulp for use in breeding programs or as rootstock for cultivation in high salinity conditions
Adaptability, stability and tolerance toof melon accessions to salinity
Keywords: Melão; Germoplasma; Salinidade; Tolerância; Melon; Germplasm; Salinity; Tolerance; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO